The role of Irfan 'Abd al-Hamid Fattah in presenting a balanced picture of 'Ilm al-Kalam for the 21st century audience - Awang Abd. Rahman @ Jusoh, Amilah (2015)
Early development of Islamic thought which is mainly on kalam is not only observed to be less interesting but also negative by nature. An observation of available literatures will easily bring to the conclusion that kalam is about irreconcilable conflicts among its schools on fundamental problems. One of the figures who has quite unique approach is Prof. Irfan Abd al-Hamid Fattah. He demonstrates his extraordinary capability in discussing issues in the hands of various schools in a very critical approach. This paper aims to study his endeavours to present kalam as a vital discipline of Islam. This is achieved by studying his methods which are found to be significant in maintaining the objectivity and balanced approach to the subject. This paper will explore solutions to several major issues in kalam namely God's attributes and human action. This discussion sheds light about the nature of disagreement on fundamental issues in Islam. Instead of viewing different views of kalam to be problematic, they are found to be invaluable contributions mainly in defending Islam from various challenges. Important lessons also can be derived from these early discourses in facing modern challenges which includes extremism and radicalism.